Positive electrode material composition, positive plate, preparation method of positive plate and lithium ion battery
By adding fast ion conductors and metal ion modified nanocellulose as emollients to the positive electrode material composition of lithium ion batteries, the problem of poor discharge performance of lithium ion batteries under low temperature conditions is solved, and a more stable and high-capacity low-temperature discharge performance is achieved, while maintaining the good performance of the battery at high temperature and circulation.
Patent Information
- Application Number
- CN202510073441.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Lithium-ion batteries have poor discharge performance under low temperature conditions, resulting in increased charging difficulties and safety risks. The existing improvement methods have limited improvements to the low-temperature performance of high-voltage system battery cells and affect electrochemical performance.
A positive electrode material composition is used, including 80 to 99 parts of the positive electrode active material, 0.1 to 20 parts of the conductive agent, 0.2 to 20 parts of the binder, 0.1 to 5 parts of the fast ion conductor, and 0.1 to 5 parts of the lubricant, among which the lubricant is metal ion modified nanocellulose. The low-temperature discharge performance of the positive electrode sheet is improved by a specific component ratio and a preparation method.
The addition of fast ion conductors and emollients maintains high ion conductivity at low temperatures, improves the migration efficiency of lithium ions, reduces the internal impedance of the battery, and improves the low-temperature discharge performance of lithium ion batteries, while not affecting the overall electrical performance of the battery, including high-temperature storage, cycling performance and safety performance.
Smart Images

Figure CN119650682A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a positive electrode material composition, a positive electrode sheet and a preparation method thereof, and a lithium-ion battery. Background Art
[0002] With the widespread application of secondary battery technology, consumer electronic products such as laptops and mobile phones have an increasing demand for low-temperature performance. However, the DC internal resistance of secondary batteries increases sharply under low temperature conditions, making it difficult to discharge or even impossible to discharge electricity. When charging under low temperature conditions, the charging constant current ratio decreases due to increased polarization, and it is impossible to fully charge; in addition, high-rate charging at low temperatures is prone to lithium deposition, which further poses a safety risk.
[0003] At present, the methods to improve low-temperature performance mainly include: improvement of positive electrode materials, optimization of electrolytes and improvement of negative electrode materials. Specifically, the improvement of positive electrode materials mainly includes: surface coating, using materials with excellent conductivity to coat the surface of the active material, improving the conductivity of the positive electrode material interface, reducing the interface impedance, while reducing the side reactions between the positive electrode material and the electrolyte, and stabilizing the material structure; bulk doping, through the bulk doping of Mn, Al, Cr, Mg, F and other elements, increasing the interlayer spacing of the material, improving Li + The diffusion rate in the body reduces the diffusion impedance; the particle size of the material is reduced, and the Li + Migration path, but will increase the specific surface area of the material, may increase the side reaction with the electrolyte. Electrolyte optimization mainly includes: adjusting the electrolyte formula, improving the low temperature conductivity of the electrolyte by optimizing the solvent composition, using new electrolyte salts, etc.; using additives, new additives can improve the properties of the SEI film, which is beneficial to Li + Conduct at low temperatures. The improvements in negative electrode materials mainly include: surface treatment, including surface oxidation and fluorination, reducing the active sites on the graphite surface, generating more micro-nanostructure pores, which are conducive to lithium ion transmission and reduce impedance; surface coating, such as carbon coating and metal coating, to avoid direct contact between the negative electrode and the electrolyte, improve compatibility, and increase conductivity; increase the distance between graphite layers, by introducing elements such as B and K, improve the graphite structure, increase the distance between layers, and improve the ability to remove / insert lithium; control the particle size. The larger the particle size, the longer the lithium ion diffusion path, the greater the impedance, and affects the low temperature performance.
[0004] In summary, these conventional methods have limited effect on improving the low-temperature performance of high-voltage battery cells, and these methods have more or less negative effects on the electrochemical performance of the battery cells. In addition, these material improvement methods are difficult for battery manufacturers. Therefore, how to improve the low-temperature performance of high-voltage battery cells while maintaining the excellent electrochemical performance of the battery cells and making it convenient for battery manufacturers to use has become a technical problem that urgently needs to be solved. Summary of the invention
[0005] The main purpose of the present application is to provide a positive electrode material composition, a positive electrode sheet and a preparation method thereof, and a lithium ion battery, so as to solve the problem of poor discharge performance of lithium ion batteries at low temperatures in the prior art.
[0006] In order to achieve the above-mentioned purpose, according to one aspect of the present application, a positive electrode material composition is provided, which comprises, by weight: 80 to 99 parts of positive electrode active material, 0.1 to 20 parts of conductive agent, 0.2 to 20 parts of binder, 0.1 to 5 parts of fast ion conductor, and 0.1 to 5 parts of wetting agent; wherein the wetting agent is metal ion modified nanocellulose.
[0007] Furthermore, the mass ratio of the positive electrode active material, the fast ion conductor and the wetting agent is 97:(1.4-2):(0.1-0.5).
[0008] Furthermore, the mass percentage of metal ions in the metal ion-modified nanocellulose is 0.05% to 1.5%; further, the metal ion-modified nanocellulose is selected from Cu 2+ Modified nanocellulose, Zn 2+ Modified nanocellulose and Co 2+ Any one or more of the modified nanocellulose; further, the metal ion-modified nanocellulose is Cu 2+ Modified nanocellulose.
[0009] Further, the fast ion conductor is selected from any one or more of LATP, LAGP, LLZO and LLZTO; further, the fast ion conductor is LATP; further, the chemical formula of LATP is Li y Al x Ti 2-x (PO4)3, wherein 1.1≤y≤1.7, 0.1≤x≤0.7; and / or, the D50 particle size of LATP is 100 to 1000 nm, further, 150 to 300 nm.
[0010] Furthermore, the above-mentioned positive electrode material composition also includes 0.01 to 20 parts of a dispersant; further, the dispersant is selected from any one or more of polyvinyl pyrrolidone, polyvinyl alcohol, polyether compounds and polyester compounds; further, the dispersant is polyvinyl pyrrolidone.
[0011] Further, the above-mentioned positive electrode active material is selected from any one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium-rich manganese-based materials, lithium iron phosphate, LiMO2 and Li2S, and M in LiMO2 is selected from any one or more of Mn, Co and Ni; and / or, the conductive agent is selected from any one or more of conductive carbon black, conductive graphite, nano-carbon fiber, carbon nanotube, graphene, carbon aerogel and conductive carbon nitride; further, the conductive agent is a combination of conductive carbon black and carbon nanotube, and the mass ratio of conductive carbon black to carbon nanotube is (0.6~1):(0.3~0.5); and / or, the binder is selected from any one or more of polyvinylidene fluoride, polytetrafluoroethylene, carboxymethyl cellulose, styrene-butadiene rubber, methyl cellulose, polyacrylic acid, polyacrylate and polyacrylonitrile; further, the binder is polyvinylidene fluoride.
[0012] According to another aspect of the present application, a positive electrode sheet is provided, comprising a positive electrode active layer and a current collector, wherein the positive electrode active layer contains the aforementioned positive electrode material composition.
[0013] According to another aspect of the present application, a method for preparing the aforementioned positive electrode sheet is provided, and the preparation method comprises the following steps: step S1, stirring and mixing a binder and an organic solvent to obtain a glue solution; step S2, first mixing the glue solution and a wetting agent to obtain a mixed slurry; step S3, sequentially mixing the mixed slurry with a conductive agent, a positive electrode active material, and a fast ion conductor to obtain a positive electrode slurry; step S4, coating the positive electrode slurry on the surface of a current collector, and sequentially drying and rolling to obtain a positive electrode sheet.
[0014] Furthermore, in the above step S2, the glue, wetting agent and dispersant are first mixed to obtain a mixed slurry; and / or, in step S1, the stirring and mixing is carried out under vacuum conditions, and the vacuum degree is -0.1 to -0.01 MPa; and / or, the stirring and mixing rotation speed is 2000 to 7000 rpm; and / or, the stirring and mixing temperature is 5 to 25°C.
[0015] According to another aspect of the present application, a lithium-ion battery is provided, comprising a positive electrode sheet, an electrolyte and a negative electrode sheet, wherein the positive electrode sheet is the positive electrode sheet mentioned above.
[0016] By applying the technical solution of the present application, the fast ion conductor can still maintain high ionic conductivity at low temperatures. The addition of the fast ion conductor helps to improve the migration efficiency of lithium ions between electrode materials, reduce the impedance inside the battery, and help the lithium ion battery to provide a more stable and higher capacity discharge in a low temperature environment. By using metal ion-modified nanocellulose as a wetting agent, the metal ion-modified nanocellulose has a unique radial ratio and abundant surface hydroxyl groups, has good solvation ability and swelling characteristics, helps to improve the wetting performance of the positive electrode sheet, and increases the liquid retention of the positive electrode sheet, thereby helping to improve the low temperature performance of the lithium ion battery. The presence of the wetting agent helps to improve the uniformity of the dispersion of the fast ion conductor in the positive electrode material, thereby helping to further improve the discharge performance of the positive electrode sheet at low temperatures. The addition of fast ion conductors and wetting agents in the present application helps to improve the low temperature discharge performance of lithium ion batteries, and does not affect the comprehensive electrical properties of the battery, including high temperature storage, cycle performance, and safety performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The drawings constituting part of the present application are used to provide a further understanding of the present application. The exemplary embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0018] Figure 1 The SEM image of the positive electrode sheet in Example 1 of the present application is shown. DETAILED DESCRIPTION
[0019] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0020] As analyzed in the background technology of this application, lithium-ion batteries in the prior art have the problem of poor discharge performance at low temperatures. In order to solve the above problem, this application provides a positive electrode material composition, a positive electrode sheet and a preparation method thereof, and a lithium-ion battery.
[0021] In a typical embodiment of the present application, a positive electrode material composition is provided, which includes, by weight: 80 to 99 parts of a positive electrode active material, 0.1 to 20 parts of a conductive agent, 0.2 to 20 parts of a binder, 0.1 to 5 parts of a fast ion conductor and 0.1 to 5 parts of a wetting agent; wherein the wetting agent is metal ion-modified nanocellulose.
[0022] Fast ion conductors can still maintain high ionic conductivity at low temperatures. The addition of fast ion conductors helps to improve the migration efficiency of lithium ions between electrode materials, reduce the impedance inside the battery, and help lithium-ion batteries provide more stable and higher capacity discharge in low temperature environments. By using metal ion-modified nanocellulose as a wetting agent, metal ion-modified nanocellulose has a unique radial ratio and abundant surface hydroxyl groups, has good solvation ability and swelling properties, helps to improve the wetting properties of the positive electrode sheet, and increases the liquid retention of the positive electrode sheet, thereby helping to improve the low-temperature performance of lithium-ion batteries. The presence of a wetting agent helps to improve the uniformity of the dispersion of fast ion conductors in the positive electrode material, thereby helping to further improve the discharge performance of the positive electrode sheet at low temperatures. The addition of fast ion conductors and wetting agents in this application helps to improve the low-temperature discharge performance of lithium-ion batteries without affecting the comprehensive electrical properties of the battery, including high-temperature storage, cycle performance, and safety performance.
[0023] In one embodiment of the present application, the mass ratio of the above-mentioned positive electrode active material, fast ion conductor and wetting agent is 97:(1.4-2):(0.1-0.5).
[0024] The positive electrode active material provides capacity and energy density for the battery. The fast ion conductor can still maintain good ion conductivity at low temperatures. It can form an efficient lithium ion transmission channel inside the battery, which helps to reduce the impedance of the battery under low temperature conditions, thereby helping to improve the low temperature discharge performance of the battery. The wetting agent can increase the liquid retention of the electrode. Under low temperature conditions, the wetting agent can promote the electrolyte penetration of lithium ions and improve the transmission efficiency of lithium ions, thereby further improving the low temperature discharge performance. Controlling the mass ratio of the positive electrode active material, fast ion conductor and wetting agent within the above range helps to give full play to the synergistic effect among the three, thereby helping to further improve the discharge performance of lithium-ion batteries at low temperatures.
[0025] In one embodiment of the present application, the mass percentage of metal ions in the above-mentioned metal ion-modified nanocellulose is 0.05% to 1.5%; in one embodiment of the present application, the metal ion-modified nanocellulose is selected from Cu 2+ Modified nanocellulose, Zn 2+ Modified nanocellulose and Co 2+ Any one or more of the modified nanocellulose; in one embodiment of the present application, the metal ion-modified nanocellulose is Cu 2+ Modified nanocellulose.
[0026] When nanocellulose is modified with metals, the molecular chain spacing is optimized, especially Cu 2+ Modified nanocellulose, Cu 2+The modified nanocellulose has a hexagonal crystal structure, with a molecular chain spacing of 0.87nm. The molecular chains are cross-linked by Cu-O bonds, which has better ion wettability, helps to increase the contact area between the electrolyte and the electrode, promotes the transmission of lithium ions, and thus helps to improve the low-temperature discharge performance of the battery. 2+ The mass content of Cu element in the modified nanocellulose is within the above range, which helps to further improve the Cu 2+ The ion wettability of the modified nanocellulose increases the liquid retention capacity of the positive electrode.
[0027] The mass percentage of metal ions in the above-mentioned metal ion-modified nanocellulose can be 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4% or 1.5%.
[0028] Preparation method of metal ion modified nanocellulose: commercial wood pulp is oxidized to obtain nanocellulose, and then the nanocellulose membrane is soaked in a NaOH solution saturated with metal ions. During the soaking process, the metal ions will interact with the functional groups on the nanocellulose molecular chain. The soaked membrane is washed with clean water, and finally the residual water molecules in the washed cellulose membrane are replaced with DMF solvent. After vacuum drying, it is soaked in a conventional electrolyte, and then vacuum dried again to obtain metal ion modified nanocellulose.
[0029] In one embodiment of the present application, the fast ion conductor is selected from any one or more of LATP, LAGP, LLZO and LLZTO; in one embodiment of the present application, the fast ion conductor is LATP; in one embodiment of the present application, the chemical formula of LATP is Li y Al x Ti 2-x (PO4)3, wherein 1.1≤y≤1.7, 0.1≤x≤0.7; and / or, the D50 particle size of LATP is 100-1000 nm. In one embodiment of the present application, the D50 particle size of LATP is 150-300 nm.
[0030] Fast ion conductors, especially LATP, have high ion conductivity under low temperature conditions. This is because LATP has a stable lattice structure and can maintain a high lithium ion mobility even when the temperature drops. Controlling y and x within the above range helps to further improve Li y Al x Ti 2-xThe ionic conductivity of (PO4)3 is improved, which helps to further improve the discharge performance of lithium-ion batteries at low temperatures. Too low D50 particle size is not conducive to reducing the probability of LATP agglomeration, and too high D50 particle size is not conducive to improving the uniformity of LATP dispersion in the positive electrode material. Controlling the D50 particle size of LATP within the above range helps to make full contact between LATP compounds and other components, which helps to further improve the discharge performance of lithium-ion batteries at low temperatures.
[0031] The D50 particle size of the LATP may be 150 nm, 200 nm, 250 nm or 300 nm. The y may be 1.1, 1.2, 1.3, 1.4, 1.5, 1.6 or 1.7; and the x may be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6 or 0.7.
[0032] In one embodiment of the present application, the above-mentioned positive electrode material composition also includes 0.01 to 20 parts of a dispersant; in one embodiment of the present application, the dispersant is selected from any one or more of polyvinyl pyrrolidone, polyvinyl alcohol, polyether compounds and polyester compounds; in one embodiment of the present application, the dispersant is polyvinyl pyrrolidone.
[0033] One of the main functions of the dispersant is to improve the rheological properties of the positive electrode slurry, keep it stable during stirring and coating, and reduce the agglomeration of components such as positive electrode active materials, conductive agents, and fast ion conductors. Polyvinyl pyrrolidone has good solubility and viscosity adjustment capabilities, and can form a stable colloidal state in the electrode slurry, promote the uniform dispersion of components, thereby helping to improve the stability of the slurry and facilitate the uniform coating and processing of the electrode.
[0034] In one embodiment of the present application, the above-mentioned positive electrode active material is selected from any one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium-rich manganese-based materials, lithium iron phosphate, LiMO2 and Li2S, and M in LiMO2 is selected from any one or more of Mn, Co and Ni; and / or, the conductive agent is selected from any one or more of conductive carbon black, conductive graphite, nano-carbon fiber, carbon nanotubes, graphene, carbon aerogel and conductive carbon nitride; in one embodiment of the present application, the conductive agent is a combination of conductive carbon black and carbon nanotubes, and the mass ratio of conductive carbon black to carbon nanotubes is (0.6~1):(0.3~0.5); and / or, the binder is selected from any one or more of polyvinylidene fluoride, polytetrafluoroethylene, carboxymethyl cellulose, styrene-butadiene rubber, methyl cellulose, polyacrylic acid, polyacrylate, and polyacrylonitrile; in one embodiment of the present application, the binder is polyvinylidene fluoride.
[0035] Controlling the types of positive electrode active materials within the above range helps to enrich the selectivity of the materials. Conductive carbon black can provide a high specific surface area, which is conducive to the formation of an electron transport network; carbon nanotubes provide efficient electron and ion transport paths with their one-dimensional nanostructure. Controlling the mass ratio of conductive carbon black and carbon nanotubes within the above range helps to build a three-dimensional conductive network, thereby helping to reduce the electron and ion transport impedance inside the electrode material. Using polyvinylidene fluoride as a binder helps to form a uniform and dense electrode coating, reduces the peeling of electrode materials during the cycle process, and helps to improve the cycle stability and service life of the battery. At the same time, polyvinylidene fluoride has a high compatibility with fast ion conductors and wetting agents, which helps to improve the stability of the battery at low temperatures.
[0036] In another typical embodiment of the present application, a positive electrode sheet is provided, comprising a positive electrode active layer and a current collector, wherein the positive electrode active layer contains the aforementioned positive electrode material composition.
[0037] Since the positive electrode active layer of the positive electrode sheet contains the positive electrode material composition of the present application, the positive electrode sheet has good low-temperature discharge performance at low temperatures.
[0038] In another typical embodiment of the present application, a method for preparing the aforementioned positive electrode sheet is provided, and the preparation method comprises the following steps: step S1, stirring and mixing a binder and an organic solvent to obtain a glue solution; step S2, first mixing the glue solution and a wetting agent to obtain a mixed slurry; step S3, sequentially mixing the mixed slurry with a conductive agent, a positive electrode active material, and a fast ion conductor to obtain a positive electrode slurry; step S4, coating the positive electrode slurry on the surface of a current collector, and then sequentially drying and rolling to obtain a positive electrode sheet.
[0039] In step S1, the binder and the organic solvent are stirred and mixed to obtain a glue solution. By preparing the glue solution in advance, the binder can be evenly dispersed in the slurry during the subsequent mixing process, thereby helping to enhance the structural stability of the positive electrode sheet during the charge and discharge process, reduce the shedding of active materials and the stratification of the electrode sheet, and thus help improve the cycle performance and safety of the battery. The step-by-step mixing in steps S2 and S3 helps to improve the uniformity and stability of the positive electrode slurry.
[0040] Including but not limited to, the above organic solvent is selected from any one or more of N-methylpyrrolidone, dimethyl carbonate, ethylene carbonate, and diethylene carbonate.
[0041] In one embodiment of the present application, an organic solvent may or may not be added in the above step S2.
[0042] In one embodiment of the present application, in the above step S3, the positive electrode active material is added in multiple times; in one embodiment of the present application, the positive electrode active material is added in three times.
[0043] In one embodiment of the present application, before using the positive electrode active material, dispersant, binder and conductive agent, the positive electrode active material, dispersant, binder and conductive agent are also pre-baked to completely remove the moisture in the positive electrode active material, dispersant, binder and conductive agent; in one embodiment of the present application, the pre-baking temperature is 80°C and the time is 8 hours.
[0044] In one embodiment of the present application, in the above-mentioned step S2, the glue, wetting agent and dispersant are first mixed to obtain a mixed slurry; and / or, in step S1, the stirring and mixing is carried out under vacuum conditions, and the vacuum degree is -0.1 to -0.01 MPa; and / or, the stirring and mixing rotation speed is 2000 to 7000 rpm; and / or, the stirring and mixing temperature is 5 to 25°C.
[0045] Controlling the vacuum degree, rotation speed and temperature within the above ranges helps to improve the dispersibility and stability of the binder in the organic solvent.
[0046] The stirring and mixing temperature may be 5°C, 10°C, 15°C or 25°C.
[0047] In another typical embodiment of the present application, a lithium-ion battery is provided, comprising a positive electrode sheet, an electrolyte and a negative electrode sheet, wherein the positive electrode sheet is the positive electrode sheet mentioned above.
[0048] The lithium-ion battery has excellent discharge performance at low temperatures, and the battery has excellent room-temperature cycle stability and high-temperature storage performance.
[0049] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.
[0050] Example 1
[0051] Nanocellulose was obtained by oxidation of commercial wood pulp, and then the nanocellulose membrane was immersed in saturated Cu 2+ In the NaOH solution, Cu 2+ The membrane is washed with clean water, and then the residual water molecules in the washed cellulose membrane are replaced with DMF solvent. After vacuum drying, it is soaked in conventional electrolyte, and then vacuum dried again to obtain Cu 2+ Modified nanocellulose, Cu 2+ Cu in modified nanocellulose 2+ The mass content is 0.05%.
[0052] 1) baking the positive electrode active material lithium cobalt oxide, the conductive agent conductive carbon black, the binder PVDF, and the dispersant PVP at 80° C. for 8 hours;
[0053] 2) In parts by weight, 0.54 parts of the PVDF binder baked in step 1) was added to 15 parts of N-methylpyrrolidone, and the mixture was stirred until the solution became transparent. During the stirring process, the vacuum degree was controlled to be -0.1 MPa, the rotation speed was 3000 rpm, and the temperature was 20° C. to obtain a PVDF solution;
[0054] 3) Take 0.06 parts of the PVP dispersant baked in step 1) and 0.1 parts of Cu 2+ The modified nanocellulose is added to the PVDF solution prepared in step 2), and then 15 parts of N-methylpyrrolidone is added, and the mixture is stirred until there are no obvious large agglomerated particles;
[0055] 4) adding 0.6 parts of the conductive carbon black baked in step 1) to the solution prepared in step 3) and stirring thoroughly;
[0056] 5) adding 100 parts of carbon nanotube solution (solid content of 0.3%, carbon nanotubes in the carbon nanotube solution by weight of 0.3 parts) to the solution prepared in step 4) and stirring thoroughly;
[0057] 6) taking 97 parts of the lithium cobalt oxide baked in step 1) and adding them into the solution prepared in step 5) in three equal portions and stirring them thoroughly;
[0058] 7) Take 7 parts of LATP solution (solid content is 20%, and the weight of LATP in the LATP solution is 1.4 parts) and add it to the slurry prepared in step 6). The chemical formula of LATP is Li 1.7 Al 0.7 Ti 1.3 (PO4)3, Li 1.7 Al 0.7 Ti 1.3 The D50 particle size of (PO4)3 is 150 nm, and the positive electrode slurry is obtained by sufficient stirring.
[0059] 8) After coating the positive electrode slurry on the surface of the current collector, drying and rolling are performed in sequence to obtain a positive electrode sheet.
[0060] Example 2
[0061] The difference from Example 1 is that the weight percentage of lithium cobalt oxide is 97 parts, Li 1.7 Al 0.7 Ti 1.3 Li in (PO4)3 solution 1.7 Al 0.7 Ti 1.3 The weight of (PO4)3 is 2 parts, Cu2+ The weight proportion of the modified nanocellulose is 0.5 parts, lithium cobalt oxide, Li 1.7 Al 0.7 Ti 1.3 (PO4)3 and Cu 2+ The mass ratio of the modified nanocellulose is 97:2:0.5, and a positive electrode sheet is finally obtained.
[0062] Example 3
[0063] The difference from Example 1 is that the weight percentage of lithium cobalt oxide is 97 parts, Li 1.7 Al 0.7 Ti 1.3 Li in (PO4)3 solution 1.7 Al 0.7 Ti 1.3 The weight percentage of (PO4)3 is 1 part, Cu 2+ The weight percentage of the modified nanocellulose is 0.6 parts, lithium cobalt oxide, Li 1.7 Al 0.7 Ti 1.3 (PO4)3 and Cu 2+ The mass ratio of the modified nanocellulose is 97:1:0.6, and a positive electrode sheet is finally obtained.
[0064] Example 4
[0065] The difference from Example 1 is that Cu 2+ The mass content of Cu element in the modified nanocellulose is 1.5%, and a positive electrode sheet is finally obtained.
[0066] Example 5
[0067] The difference from Example 1 is that Cu 2+ The mass content of Cu element in the modified nanocellulose is 2%, and a positive electrode sheet is finally obtained.
[0068] Example 6
[0069] The difference from Example 1 is that Li 1.7 Al 0.7 Ti 1.3 The D50 particle size of (PO4)3 is 300nm, and the positive electrode sheet is finally obtained.
[0070] Example 7
[0071] The difference from Example 1 is that Li 1.7 Al 0.7 Ti 1.3 The D50 particle size of (PO4)3 is 100nm, and the positive electrode sheet is finally obtained.
[0072] Example 8
[0073] The difference from Example 1 is that the chemical formula of LATP is Li 1.1 Al 0.1 Ti 1.9 (PO4)3, and finally the positive electrode is obtained.
[0074] Example 9
[0075] The difference from Example 1 is that the chemical formula of LATP is Li 1.8 Al 0.8 Ti 1.2 (PO4)3, and finally the positive electrode is obtained.
[0076] Example 10
[0077] The difference from Example 1 is that the weight portion of the conductive carbon black is 1 part, the mass portion of the carbon nanotubes in the carbon nanotube solution is 0.5 parts, and the mass ratio of the conductive carbon black to the carbon nanotubes is 1:0.5, and finally a positive electrode sheet is obtained.
[0078] Embodiment 11
[0079] The difference from Example 1 is that the weight portion of the conductive carbon black is 0.6 parts, the mass portion of the carbon nanotubes in the carbon nanotube solution is 0.6 parts, the mass ratio of the conductive carbon black to the carbon nanotubes is 0.6:0.6, and finally a positive electrode sheet is obtained.
[0080] Example 12
[0081] The difference from Example 1 is that the vacuum degree of stirring and mixing is -0.01 MPa, the rotation speed of stirring and mixing is 2000 rpm, and the temperature of stirring and mixing is 5° C., and finally a positive electrode sheet is obtained.
[0082] Embodiment 13
[0083] The difference from Example 1 is that the vacuum degree of stirring and mixing is -0.1 MPa, the rotation speed of stirring and mixing is 7000 rpm, and the temperature of stirring and mixing is 25° C., and finally a positive electrode sheet is obtained.
[0084] Embodiment 14
[0085] The difference from Example 1 is that the vacuum degree of stirring and mixing is -0.005 MPa, the rotation speed of stirring and mixing is 1000 rpm, the temperature of stirring and mixing is 30° C., and finally a positive electrode sheet is obtained.
[0086] Embodiment 15
[0087] The difference from Example 1 is that Zn 2+ Modified nanocellulose replaces Cu 2+ The modified nanocellulose finally obtains the positive electrode.
[0088] Example 16
[0089] The difference from Example 1 is that Co 2+ Modified nanocellulose replaces Cu 2+ The modified nanocellulose finally obtains the positive electrode.
[0090] Comparative Example 1
[0091] The difference from Example 1 is that Cu 2+ The modified nanocellulose is added to finally obtain a positive electrode.
[0092] Comparative Example 2
[0093] The difference from Example 1 is that the addition of LATP solution is eliminated, and a positive electrode sheet is finally obtained.
[0094] Comparative Example 3
[0095] The difference from Example 1 is that the LATP solution and Cu 2+ The modified nanocellulose is added to finally obtain a positive electrode.
[0096] The positive electrode sheets prepared in the embodiment and the comparative example were assembled into lithium-ion batteries for low-temperature discharge capacity retention, 60°C storage for 14 days, 45°C cycling, and 25°C cycling tests.
[0097] Low-temperature discharge capacity retention rate: place the lithium-ion battery at 25°C, discharge the lithium-ion battery to a voltage of 3.4V at a rate of 0.1C, and record the discharge capacity at 25°C; place the lithium-ion battery at -20°C, discharge the lithium-ion battery to a voltage of 3.4V at a rate of 0.1C, and record the discharge capacity at -20°C. The capacity retention rate at -20°C = (discharge capacity at -20°C / discharge capacity at 25°C) × 100%; place the lithium-ion battery at -10°C, discharge the lithium-ion battery to a voltage of 3.4V at a rate of 0.1C, and record the discharge capacity at -10°C. The capacity retention rate at -10°C = (discharge capacity at -10°C / discharge capacity at 25°C) × 100%.
[0098] 14 days storage at 60℃: 1) Leave for 1min; discharge at 0.2C constant current to 2.75V; 2) Leave for 10min; charge at 0.2C constant current and constant voltage to 4.47V, cut off at 0.02C; 3) Leave for 10min; discharge at 0.2C constant current to 2.75V; 4) Leave for 10min; charge at 0.2C constant current and constant voltage to 4.47V, cut off at 0.02C; 5) After charging, the battery is placed in a 60℃ constant temperature box for 14 days Then stand at room temperature for 2h; 6) Stand for 1min; 0.2C constant current discharge to 2.75V; 7) Stand for 10min; 0.2C constant current constant voltage charge to 4.47V, 0.02C cut-off; 8) Stand for 10min; 0.2C constant current discharge to 2.75V; Capacity retention rate = (6th step discharge capacity / 3rd step discharge capacity) × 100%; Capacity recovery rate = (8th step discharge capacity / 3rd step discharge capacity) × 100%
[0099] 45℃ cycle: 1) Pretreatment: Test the initial half-charged voltage, internal resistance and thickness of the battery at 25℃; charge to 4.47V at 0.5C constant current and constant voltage, cut off at 0.05C, and test the full-charged voltage, internal resistance and thickness; 2) Set aside for 10 minutes; discharge to 3.0V at 1C constant current; 3) Set aside for 10 minutes; charge to 4.47V at 2C constant current and constant voltage, cut off at 0.05C; 4) Set aside for 10 minutes; discharge to 3.0V at 1C constant current; 5) Place the battery in a 45℃ constant temperature box and repeat 3) to 4) for 200 cycles; 6) Charge to 4.47V at 1C constant current and constant voltage, cut off at 0.1C; 7) Test the full-charged voltage, internal resistance and thickness of the battery. Capacity retention rate = (discharge capacity at the 200th cycle / discharge capacity at the 1st cycle) × 100%; expansion rate = (full-charge thickness of the battery cell at the 200th cycle / initial half-charge thickness of the battery cell) × 100%.
[0100] 25℃ cycle: 1) Pretreatment: Test the initial half-charge voltage, internal resistance, and thickness of the battery; 0.5C constant current and constant voltage charge to 4.47V, 0.05C cut-off, test the full-charge voltage, internal resistance, and thickness; 2) Stand for 10 minutes; 1C constant current discharge to 3.0V; 3) Stand for 10 minutes; 2C constant current and constant voltage charge to 4.47V, 0.05C cut-off; 4) Stand for 10 minutes; 1C constant current discharge to 3.0V; 5) Place the battery in a 25℃ constant temperature box and repeat 3) to 4) for 200 cycles; 6) 1C constant current and constant voltage charge to 4.47V, 0.1C cut-off; 7) Test the full-charge voltage, internal resistance, and thickness of the battery. Capacity retention rate = (discharge capacity of the 200th cycle / discharge capacity of the first cycle) × 100%; expansion rate = (full-charge thickness of the battery at the 200th cycle / initial half-charge thickness of the battery) / ×100%.
[0101] The results of the capacity retention rate of lithium-ion batteries at -20°C, the capacity retention rate at -10°C, the capacity retention rate and capacity recovery rate stored at 60°C for 14 days, the capacity retention rate and expansion rate after 200 cycles at 45°C, and the capacity retention rate and expansion rate after 200 cycles at 25°C are shown in Table 1.
[0102] Table 1
[0103]
[0104]
[0105] It can be seen from Table 1 that the capacity retention rate of the positive electrode material of the embodiment at -20°C is significantly better than that of the comparative example, while its performance at room temperature or even high temperature is not affected, which indicates that the positive electrode material of the present application is suitable for a wider temperature range.
[0106] Figure 1 This is the SEM image of the positive electrode sheet in Example 1 of the present application, from Figure 1 It can be seen that the components in the positive electrode active layer are evenly distributed.
[0107] From the above description, it can be seen that the above embodiments of the present application achieve the following technical effects:
[0108] Fast ion conductors can still maintain high ionic conductivity at low temperatures. The addition of fast ion conductors helps to improve the migration efficiency of lithium ions between electrode materials, reduce the impedance inside the battery, and help lithium-ion batteries provide more stable and higher capacity discharge in low temperature environments. By using metal ion-modified nanocellulose as a wetting agent, metal ion-modified nanocellulose has a unique radial ratio and abundant surface hydroxyl groups, has good solvation ability and swelling properties, helps to improve the wetting properties of the positive electrode sheet, and increases the liquid retention of the positive electrode sheet, thereby helping to improve the low-temperature performance of lithium-ion batteries. The presence of a wetting agent helps to improve the uniformity of the dispersion of fast ion conductors in the positive electrode material, thereby helping to further improve the discharge performance of the positive electrode sheet at low temperatures. The addition of fast ion conductors and wetting agents in this application helps to improve the low-temperature discharge performance of lithium-ion batteries without affecting the comprehensive electrical properties of the battery, including high-temperature storage, cycle performance, and safety performance.
[0109] The above are only embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A positive electrode material composition, characterized in that: In parts by weight, the positive electrode material composition comprises: 80 to 99 parts of positive electrode active material; 0.1 to 20 parts of a conductive agent; 0.2 to 20 parts of a binder; 0.1 to 5 parts of a fast ion conductor; 0.1 to 5 parts of a wetting agent; Wherein, the wetting agent is metal ion modified nanocellulose.
2. The positive electrode material composition according to claim 1, characterized in that The mass ratio of the positive electrode active material, the fast ion conductor and the wetting agent is 97:(1.4-2):(0.1-0.5).
3. The positive electrode material composition according to claim 1 or 2, characterized in that: The mass percentage of metal ions in the metal ion-modified nanocellulose is 0.05% to 1.5%; preferably, the metal ion-modified nanocellulose is selected from Cu 2+ Modified nanocellulose, Zn 2+ Modified nanocellulose and Co 2+ Any one or more of the modified nanocellulose; further preferably, the metal ion modified nanocellulose is the Cu 2+ Modified nanocellulose.
4. The positive electrode material composition according to any one of claims 1 to 3, characterized in that The fast ion conductor is selected from any one or more of LATP, LAGP, LLZO and LLZTO; Preferably, the fast ion conductor is the LATP; further preferably, the chemical formula of the LATP is Li y Al x Ti 2-x (PO4)3, where 1.1≤y≤1.7, 0.1≤x≤0.7; And / or, the D50 particle size of the LATP is 100 to 1000 nm, preferably 150 to 300 nm.
5. The positive electrode material composition according to any one of claims 1 to 4, characterized in that: The positive electrode material composition further includes 0.01 to 20 parts of a dispersant; preferably, the dispersant is selected from any one or more of polyvinyl pyrrolidone, polyvinyl alcohol, polyether compounds and polyester compounds; further preferably, the dispersant is polyvinyl pyrrolidone.
6. The positive electrode material composition according to any one of claims 1 to 5, characterized in that: The positive electrode active material is selected from any one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium-rich manganese-based materials, lithium iron phosphate, LiMO2 and Li2S, and M in the LiMO2 is selected from any one or more of Mn, Co and Ni; And / or, the conductive agent is selected from any one or more of conductive carbon black, conductive graphite, nanocarbon fiber, carbon nanotube, graphene, carbon aerogel and conductive carbon nitride; preferably, the conductive agent is a combination of the conductive carbon black and the carbon nanotube, and the mass ratio of the conductive carbon black to the carbon nanotube is (0.6-1):(0.3-0.5); And / or, the binder is selected from any one or more of polyvinylidene fluoride, polytetrafluoroethylene, carboxymethyl cellulose, styrene-butadiene rubber, methyl cellulose, polyacrylic acid, polyacrylate, and polyacrylonitrile; preferably, the binder is polyvinylidene fluoride.
7. A positive electrode sheet, comprising a positive electrode active layer and a current collector, characterized in that: The positive electrode active layer contains the positive electrode material composition according to any one of claims 1 to 6.
8. A method for preparing a positive electrode sheet according to claim 7, characterized in that: The preparation method comprises the following steps: Step S1, stirring and mixing a binder and an organic solvent to obtain a glue solution; Step S2, first mixing the glue solution and the wetting agent to obtain a mixed slurry; Step S3, sequentially mixing the mixed slurry with a conductive agent, a positive electrode active material, and a fast ion conductor to obtain a positive electrode slurry; Step S4, coating the positive electrode slurry on the surface of the current collector, and then drying and rolling the positive electrode slurry to obtain the positive electrode sheet.
9. The preparation method according to claim 8, characterized in that: In the step S2, the glue solution, the wetting agent and the dispersant are mixed to obtain the mixed slurry; And / or, in step S1, the stirring and mixing is performed under vacuum conditions, and the vacuum degree is -0.1 to -0.01 MPa; And / or, the rotation speed of the stirring and mixing is 2000-7000 rpm; and / or, the temperature of the stirring and mixing is 5-25°C.
10. A lithium ion battery comprising a positive electrode, an electrolyte and a negative electrode, characterized in that: The positive electrode sheet is the positive electrode sheet according to claim 7.
Citation Information
Patent Citations
Flexible lithium ion battery electrode plate with self supporting capability and preparation method thereof
CN105633343A
Lithium ion battery silicon-containing negative electrode slurry as well as preparation method and application thereof
CN114614010A
Ion-conducting structures, devices including ion-conducting structures, and methods of use and manufacture thereof
CN114730903A
Positive plate as well as preparation method and application thereof
CN114784223A
Positive pole piece, electrochemical device and electronic device
CN116111095A